Evaluation of serial crystallographic structure determination within megahertz pulse trains - Oleksandr Yefanov; Dominik Oberthür; Richard Bean; Max O. Wiedorn; Juraj Knoska; Gisel Pena; Salah Awel; Lars Gumprecht; Martin Domaracky; Iosifina Sarrou; P. Lourdu Xavier; Markus Metz; et al. (Structural Dynamics, 2019)
The new European X-ray Free-Electron Laser (European XFEL) is the first X-ray free-electron laser capable of delivering intense X-ray pulses with a megahertz interpulse spacing in a wavelength range suitable for atomic resolution structure determination. An outstanding but crucial question is whether the use of a pulse repetition rate nearly four orders of magnitude higher than previously possible results in unwanted structural changes due to either radiation damage or systematic effects on data quality. Here, separate structures from the first and subsequent pulses in the European XFEL pulse train were determined, showing that there is essentially no difference between structures determined from different pulses under currently available operating conditions at the European XFEL.